Volatility connectedness of major cryptocurrency: The role of geopolitical risk - Sin, Yi Feng (2023)
This thesis aims to examine the relationship between geopolitical risk and volatility connectedness of five cryptocurrencies, namely Bitcoin (BTC), Ethereum (ETH), Ripple (XRP), Dogecoin (DOGE) and Cardano (ADA). Prices and trading volume data of these five cryptocurrencies are collected from Yahoo Finance. The research uses monthly data spanning from February 2018 to October 2022. An additional analysis was also performed using daily data from 1st January 2021 to 31st December 2021. This study uses the TVP-VAR model to calculate the monthly and daily volatility connectedness indices of the five cryptocurrencies. In terms of the level of connectedness, the monthly volatility connectedness was rather high at 74.87% compared to the 2021 daily volatility connectedness at 68.63%. The resulting monthly volatility connectedness index is further utilised as the dependent variable to examine the effect of geopolitical risk (GPR) on the level of volatility connectedness among these five cryptocurrencies. In discovering this relationship, time series approach was applied by using E-Views software. The key independent variable in this study – GPR, shows a positive and significant impact on the volatility connectedness of the five cryptocurrencies. The estimation of the relationship between GPR and volatility connectedness is controlled by Global Economic Policy Uncertainty (GEPU), Volatility Index (VIX), World Return (W_RETURN), and Energy Return (E_RETURN), which are found to be insignificant in explaining volatility connectedness. Instead, volatility connectedness of these five cryptocurrencies is more likely to be affected by their own trading activity such as the return (AVERET) and volume (AVEVOL) which are also included in this study as control variables. Findings of this research can be utilized by investors who invest in cryptocurrencies market to guide their risk management and diversification strategies. Moreover, the connectedness index of the five cryptocurrencies can provide insights into their potential impact on each other's price movements, and investors can use this information to guide their investment decisions.